Favorable nucleation and continuous regulation direct uniform and oblate Li deposition. Issue 4 (5th January 2023) - Liu, Chen; Sun, Shuting; Jin, Shan; Lin, Tianning; Ding, Fei; Li, Ruhong; Dai, Changsong
Abstract : This work reports a more uniform and oblate Li plating morphology assisted by ZnS-rich matrix and proposes the dynamic bi-phasic regulation mechanism. Abstract : Constructing three-dimensional (3D) current collectors has been revealed as an effective strategy to suppress lithium dendrites and extend the lifespan of Li metal batteries. Earlier attempts to improve Li compatibility have focused on the initial lithium nucleation to increase lithiophilic sites and maximize the electrochemically active areas. However, the subsequent Li growth process and the evolution of the regulation mechanism, which also govern the Li plating behavior, have not beenpreviously exploited in depth. Herein, we report a full-process-adjusted zinc sulfide (ZnS)-rich carbon-based matrix enabling more uniform and oblate Li plating morphology. At the early stage, the in situ formed LiZn alloy offers the lithiophilic region for favorable nucleation and initial deposition while the Li2 S component passivates the micro-interface. As plating progresses, the proportion of solid solution (Li1− x Zn x ) in the conductive substrate gradually increases, replacing LiZn to dominate the deposition morphology. The electrochemical tests confirm the excellent performance of the modified matrix with nano-ZnS decoration, which delivers a high average Coulombic efficiency of about 99% for 100 cycles. Our work furnishes an alternative choice from the sustainable perspective of adjusting Li plating behavior for dendrite-free and long-term Li metal batteries.